The Mountain of Youth: Converting American Buddhism and the Authority of the Monk-Convert Paradigm. (1st January 2019) - Baker, Drew
Abstract English: This article examines generational shifts in popular narratives pertaining to dominant formations of Buddhism in the United States from 1950 to the 1990s through a postcolonial lens particularly sensitive to age, children, and family dynamics. A close read of Jack Kerouac's novels and the film Little Buddha identifies important features of this genealogy. This analysis shows that white Buddhist American converts' power and visibility have been reinforced by the Orientalist notion of a monk-convert lineage which presents the convert—represented as a free white young adult—as the sole heroic incarnation of the present and future of Buddhism in the modern world. Key words: Buddhism, Conversion, Religion and Age, Orientalism